Functional evaluation of immunoregulatory molecules HLA-G, galectin-1, and IL-10 in people living with HIV. Issue 2 (14th January 2022) - Cortelette, Natalia Alves; Souza, Nayana De Oliveira; Cataldi-Rodrigues, Lilian; Arthur, Connie; Stowell, Sean R.; Dias-Baruffi, Marcelo; Guimarães, Daniela Amorim Melgaço; Ayres, Lorena Rocha; Trés Pancoto, João Alexandre
Abstract: Objective(s): Investigate polymorphisms and expressions of human leukocyte antigen-G (HLA-G), galectin-1 (Gal-1), and interleukin-10 (IL-10) in people living with HIV (PLHIV) with and without comorbidities to help understanding the mechanisms involved in triggering these disorders in PLHIV and in their prognosis. Design: Here we evaluated the potential correlation between the genetic polymorphism and/or protein levels of HLA-G, Gal-1, and IL-10 with and without comorbidities of PLHIV. Methods: Two hundred HIV patients under antiretroviral treatment (83 with comorbidities and 117 without comorbidities) and 200 healthy individuals (controls) were genotyped, using PCR, for HLA-G 14-base pair polymorphism located at the 3' untranslated region in exon 8 insertion/insertion (Ins/Ins: low HLA-G expression) or deletion/deletion (Del/Del: high HLA-G expression). Soluble levels of HLA-G (sHLA-G), Gal-1, and IL-10 were quantified by enzyme-linked immunosorbet assay. Results: HIV patients without comorbidities exhibited higher frequency of 14-base pair Del/Del genotype than HIV patients with comorbidities. As expected, HIV patients Ins/Ins with and without comorbidities produced less sHLA-G than controls. However, HIV patients Del/Del with comorbidities expressed sHLA-G more than controls and HIV patients Del/Del without comorbidities. Interestingly, patients that showed low levels sHLA-G, and presence of comorbidities, exhibited high Gal-1 serum levels. However, an increase in soluble levels of IL-10 in PLHIV was observed when compared to controls, especially in the PLHIV group without comorbidities suggesting, a protective role of IL-10 in the development of comorbidities. Conclusions: These data suggested that the high expression of sHLA-G and IL-10 or Gal-1 could be associated and could be associated with the development or not of comorbidities in PLHIV.